PELUANG PENGEMBANGAN JAGUNG PADA GAWANG KELAPA DALAM UPAYA PENINGKATAN PRODUKSI JAGUNG DI SUMATERA BARAT - Yulinar Zubaidah; Zainal Lamid; Ridwan Ridwan (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2004)
The national maize necessity directly increase in the last few years. On the years 1996-2000 periods rate of maize import was about 52,08 % per year. The amount of national maize need for feeding increased approximately 52,4% of food derived from maize to increase the national maize production by expansions of maize hybrid and composite. However their development on the former still slowly. The production increasing from 1996 to 2001 0,17% on year and maize productivity about 2,67 t/ha. In the west sumatera by exspansion maize planting area and utilization of land area more efficient, and include land area either coconut plant. West sumatera province had coconut plantation would total area 91,920 ha. And spreahed in some regensi and city. The result of the experiment and assessment in west sumatera BPTP. In land area inter coconut plant plant can be growth maize C5,C7 and C9 hybrids and yield average about 5,0 6,7 t/ha in 50 kota dan Padang Pariaman regency with r/c ratio 1,9 2,5. From the result of research and assessment of west sumatera BPTP. Application of land area inter coconut plant had opportunity to increase maize production in West Sumatera. Keywords: Extensifikasi,Expansions of maize hybrid, composite